2017
DOI: 10.2989/16085906.2017.1345768
|View full text |Cite
|
Sign up to set email alerts
|

Constrained relationship agency as the risk factor for intimate partner violence in different models of transactional sex

Abstract: Women who engage in transactional sex are more likely to experience intimate partner violence (IPV) and are at higher risk of HIV. However, women engage in transactional sex for a variety of reasons and the precise mechanism linking transactional sex and IPV is not fully understood. We conducted a behavioural survey with a cross-sectional sample of 401 women attending 1 rural and 1 urban public antenatal clinic in Swaziland between February and June 2014. We used structural equation modelling to identify and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 48 publications
(65 reference statements)
0
17
0
Order By: Relevance
“…In our research, women recast gifts bestowed by lovers as being valuable not because of their economic value, but because of the emotional currency of such gifts as demonstrations of love. In fact, Fielding-Miller and Dunkle’s (2017) research with Swazi women finds that there are very real emotional benefits to receiving gifts, in that women who receive more gifts are less likely to report emotional IPV.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our research, women recast gifts bestowed by lovers as being valuable not because of their economic value, but because of the emotional currency of such gifts as demonstrations of love. In fact, Fielding-Miller and Dunkle’s (2017) research with Swazi women finds that there are very real emotional benefits to receiving gifts, in that women who receive more gifts are less likely to report emotional IPV.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Fielding-Miller and Dunkle’s (2017) research of transactional sex in Swaziland found that love was protective against IPV, in that women who reported having sex with a partner for reasons other than love or affection (such as poverty, money, hunger, fear of abandonment, or violence) had increased odds of emotional, physical, and sexual violence. Starmann and colleagues (2016) assessed processes of change among couples exposed to the SASA!…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Social and structural drivers also strongly influence women's risk of experiencing IPV: Women in the Kingdom of Eswatini (Swaziland) and Botswana who reported food insufficiency were more likely to report forced sex in the previous 12 months [20], and a relatively large body of evidence from sub-Saharan Africa suggests that personal and familial food insecurity is associated with hazardous transactional sex, which in turn is frequently associated with higher rates of violence [5,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%